Cezary Biernacki – historyk, bibliofil i bibliograf, współpracownik redakcji Encyklopedii Powszechnej Orgelbranda – jako symbol swojej epoki - Andrysiak , Ewa (Acta Universitatis Lodziensis. Folia Librorum, 2009)
This article remembers the life and activity of Cezary Biernacki (1827-1896), a historian of Kalisz and surrounding region, who played his part in some important works of the 19th century: Orgelbrand Universal Encyclopaedia and The Geographic Dictionary of the Kingdom of Poland and other Slav countries. The topics of consideration are also the bibliography works and publishing activity of Biernacki and his bibliophile passion and the history of his library.